2020
DOI: 10.1002/hbm.25226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated menstrual pain on empathic neural responses in women with primary dysmenorrhea across the menstrual cycle

Abstract: Primary dysmenorrhea (PDM) is cyclic menstrual pain in the absence of pelvic anomalies, and it is thought to be a sex-hormone related disorder. Existing study has focused on the effects of menstrual cramps on brain function and structure, ignoring the psychological changes associated with menstrual pain. Here we examined whether pain empathy in PDM differs from healthy controls (HC) using task-based functional magnetic resonance imaging (fMRI). Fifty-seven PDM women and 53 matched HC were recruited, and data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 73 publications
4
13
0
Order By: Relevance
“…It is necessary to note that empathy is a multifaceted construct and consists of an emotional system and a cognitive system (27). The present theories propose that empathy relies strongly on the involvement of various neural networks (22), and is mediated by different series of interaction regions (28). Based on the multivariable analysis of PLS correlation, our study was consistent with the above, and further suggested a comprehensive interaction network related to different aspects of empathy.…”
Section: Trait Empathy-related Brain Functional Network In Hcssupporting
confidence: 86%
See 1 more Smart Citation
“…It is necessary to note that empathy is a multifaceted construct and consists of an emotional system and a cognitive system (27). The present theories propose that empathy relies strongly on the involvement of various neural networks (22), and is mediated by different series of interaction regions (28). Based on the multivariable analysis of PLS correlation, our study was consistent with the above, and further suggested a comprehensive interaction network related to different aspects of empathy.…”
Section: Trait Empathy-related Brain Functional Network In Hcssupporting
confidence: 86%
“…and precuneus. Functional neuroimaging studies on the neural mechanisms of empathy highlighted the AI, IFG, and IPL as parts of common networks in empathy for pain (22). Neuropsychological data provided further evidence that the lesions that involved the AI (23) and IFG (24) were associated with impairments of empathy.…”
Section: Trait Empathy-related Brain Functional Network In Hcsmentioning
confidence: 85%
“…There is also some evidence of an association between structural and functional brain alterations [61] and abnormal reward neural system connectivity in patients with primary dysmenorrhoea [62]. These changes may be associated with the abnormal empathy observed in women with primary dysmenorrhoea, regardless of their phase of the menstrual cycle [63,64]. Along with catastrophising, these neurological aspects can significantly affect the experience and intensity of pain that is perceived by women with primary dysmenorrhoea [65].…”
Section: Discussionmentioning
confidence: 99%
“…However, PD not only affects the quality of life during menstrual periods but also has an effect on psychological changes, such as pain perception, trait empathy, anxiety, depression, etc. [ 10 , 11 , 12 ]. In addition, some studies even showed the altered white matter microarchitecture and altered posterior cerebellar lobule connectivity with the perigenual anterior cingulate cortex [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%